SEASONAL DISCREPANCY IN PHENOLIC CONTENT AND ANTIOXIDANT PROPERTIES FROM BARK OF NOTHAPODYTES NIMMONIANA (GRAH.) MABB. - SANDEEP R. PAI; MANSINGRAJ S. NIMBALKAR; NILESH V. PAWAR; RAJARAM P. PATIL; GHANSHAM B. DIXIT (International Journal of Pharma and Bio Sciences, 2010)
Seasonal discrepancy in the antioxidant potential from bark of Nothapodytes nimmoniana was evaluated using two different methods (DPPH and FRAP) and were related to total phenolic content as well as flavonoid content. Higher yield of phenolic and flavonoid were observed during summer (May) similarly, the antioxidant activities (DPPH & FRAP) also were high. The antioxidant activities were strongly correlated with total phenolics (DPPH, FRAP) in all seasons, the maximum being during the summer (May) and minimum during monsoon (August). Total phenolic content showed highest correlation with DPPH and FRAP antioxidant assays during the month of winter (December). A specific pattern of increase from August-December-May was observed in phenolic content and antioxidant activities (FRAP and DPPH) tested for respective standards.